Flood Hazard Level Analysis of Kapuas Hulu Sub-watershed Using Geographic Information System - Simanjuntak, Nunut Rialdi; Umar, Umar; Gunarto, Danang; Soeryamassoeka, S. B. (Jurnal Teknik Sipil, 2024)
This article analyzes the flood hazard level in the Kapuas Hulu Sub-watershed using a Geographic Information System (GIS). The flood risk in this region is influenced by various factors such as soil types, land cover, elevation, slope, rainfall, and human activities. Ultisol (64.44%) significantly contributes to flood risk due to its low water permeability, leading to surface runoff during heavy rain. Inceptisol (31.73%) also plays a role in flood dynamics, with its water retention capacity dependent on vegetation. Smaller areas of Histosol (0.50%) and Spodosol (0.07%) pose localized flooding risks in lowland regions. The dominant land cover, primarily dryland forest, helps mitigate flooding, while settlements and agricultural zones increase vulnerability by reducing water absorption. Low-lying areas (50-100 meters) and steep slopes (25-45%) further exacerbate flood potential"”areas receiving moderate to high rainfall increase surface runoff and flood risk. GIS-based analysis categorizes flood vulnerability into low, medium, and high levels, with 57.71% of the area classified as low vulnerability. Recommendations for flood risk mitigation include soil conservation, reforestation, sustainable land management, and drainage system improvements in vulnerable areas.